Pengawasan Bagi Warga Negara Asing Di Kantor Imigrasi Kelas II Parepare - Rachmat, Edy; Sudarmi, Sudarmi; Nasrulhaq, Nasrulhaq (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
The purpose of this study was knowing preliminary control, concurrent control, and feedback for foreign citizens at the pare-pare class II immigration office. A qualitative kind of research with a data source consists of primary data and secondary data. The informant is made up of six people from the immigration office. Data-collection techniques use observation, interviews and documentation. The technique of data analysis is data reduction, data presentation, verification of data and deduction withdrawal..  The results of the study shows that supervision for foreign nationals has been actualized in policy, namely by conducting periodic surveillance of foreign nationals who are already in the working area of Class II Pare-pare immigration authorities and conducting checks on foreign nationals who will enter Indonesian territory more  precisely the working area of Kanim Parepare.